Fierce climate, sacred ground: an ethnography of climate change in Shishmaref, Alaska - Marino, Elizabeth, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2015)
Fierce Climate, Sacred Ground is an ethnographic account of the impacts of climate change in Shishmaref, Alaska. In this small Iupiaq community, flooding and erosion are forcing community members to consider relocation as the only possible solution for long-term safety. However, a tangled web of policy obstacles, lack of funding, and organizational challenges leaves the community without a clear way forward, creating serious questions of how to maintain cultural identity under the new climate regime. Elizabeth Marino analyzes this unique and grounded example of a warming world as a confluence of political injustice, histories of colonialism, global climate change, and contemporary development decisions. The book merges theoretical insights from disaster studies, political analysis, and passages from field notes into an eminently readable text for a wide audience. This is an ethnography of climate change; a glimpse into the lived experiences of a global phenomenon.
Chapter 1: It's the End of the World, and Shishmaref Is Everywhere -- Chapter 2: Unnatural Natural Disasters -- Chapter 3: Flooding and Erosion in Shishmaref: The Anatomy of a Climate Change Disaster -- Chapter 4: Seal Oil Lamps and Pre-Fab Housing: A History of Colonialism in Shishmaref -- Chapter 5: Finding a Way Forward: Trust, Distrust, and Alaska Native Relocation Planning in the Twenty-first Century -- Chapter 6: The Tenacity of Home -- Chapter 7: The Ethics of Climate Change.
Keywords: Human beings -- Effect of climate on -- Alaska -- Shishmaref; Ethnology -- Alaska -- Shishmaref; Climatic changes -- Alaska -- Shishmaref; Inupiat -- Alaska -- Shishmaref; Shishmaref (Alaska) -- Maps